SURVEY OF FOG COMPUTING - Gámez Picó, Liz; Anías Calderón , Caridad (Telemática, 2022)
The Fog Computing paradigm emerges as a solution to the growing demand of Internet of Things applications for shorter response times and greater security, as well as the proliferation of IoT devices, sensors and actuators. Currently it is a challenge to stay updated on the subject since the technology is in development and new implementations of it are being carried out. The objective of this work is to update the state of the art of technology, for which the main characteristics of the FC paradigm were defined, as well as the advances, development trends, and its current application. In addition, the OpenFog reference architecture was analyzed, the main applications of this technology were detailed, and insufficiently studied aspects such as CF management, implementation and simulation were addressed.